EVALUATION ANALYSIS ON A TEXTBOOK ENTITLED “CAMBRIDGE ENGLISH IDIOM IN USE ADVANCED” - testiana deni wijayatiningsih (Faculty of Humanities, Universitas Jenderal Soedirman, 2018)
This study discussed about an evaluation of textbook analysis entitled “Cambridge English Idiom in Used Advanced” written by written by Felicity O’Dell and Michael McCarthy. In this study, the textbook was analyzed using rubric of textbook evaluation in term of layout and design, activities, language type, materials, subject and content. From the discussion, it can be concluded that the book is suitable for advanced learner in term of the composition, given example, exercises and context.